Influence of Effective School Leadership on Teachers’ Performance: A Systematic Literature Review - Punzalan, Andrea; De Jesus , Leonora (Journal of Interdisciplinary Perspectives, 2024)
This systematic literature review examines the impact of effective school leadership on teachers' performance, focusing on various leadership styles and practices. It has been demonstrated that good leadership has a favorable impact on teachers' performance. This leadership is typified by establishing clear ideas and goals, offering assistance, cultivating a positive school culture, implementing effective communication, and inspiring respect and trust. A dearth of longitudinal studies, contradictory results, and little research conducted in various circumstances are among the notable gaps in the literature that the review points out. Research gaps can be filled, and the scope of the study can be widened so that stakeholders in education have a deeper knowledge of how various leadership methods and styles impact teachers' effectiveness. Using this knowledge, methods to improve school leaders' efficacy will be developed, ultimately improving student learning results.